Genetic identification of an invasive plant (Parthenium hysterophorus) and its crude extract phytotoxicity against palm oil weed (Diodia ocimifolia) - Zainuddin, Noorul Jannah; Salim, Norazlinaliza; Asib, Norhayu; Ashari, Siti Efliza; Omar, Dzolkhifli; Cheng, Gwendoline Lian Ee (Instytut Ochrony Roslin,Institute of Plant Protection, 2022)
This paper reports a study on genetic identification of Parthenium hysterophorus and the ability of P. hysterophorus crude extract (PHCE) to inhibit germination of weeds in palm oil plantations, particularly slender buttonweed (Diodia ocimifolia). Parthenium hysterophorus is a noxious plant with invasive properties. It has become one of the world’s seven most devastating and hazardous weed s due to its allelopathic properties. However, a compre hensive study on its genetic identification and its herbicidal activity against weeds in palm oil plantations had never been carried out. In the present study, internal transcribes spacer (ITS) region-based analysis was used as a molecular marker to ascertain the local Rumput Miang Mexico (RMM) as a P. hysterophorus species. From the results, the DNA sequence obtained was 99% matched with P. hysterophorus species database. In the dose-response bioassay study, the phytotoxicity of PHCE on D. ocimifolia was simulated under laboratory conditions. Methanolic extract of P. hysterophorus significantly inhibited germination and growth of shoots and radicles of D. ocimifolia at low concentrations (1−5 g ∙ l−1). A study on the herbicidal activity of PHCE could be an additional management approach for this phy totoxic species and an alternative way to naturally control weeds on palm oil plantations.